2019
DOI: 10.1590/0104-1428.04018
|View full text |Cite
|
Sign up to set email alerts
|

Gamma irradiation effects on polycaprolactone/zinc oxide nanocomposite films

Abstract: Polycaprolactone (PCL) to which has been added zinc oxide nanoparticles (ZnO NPs) produces nanocomposites (PCL/ZnO NCs). These nanocomposites can be used in biomedical applications and in the food packaging sector. However, for these materials to be used in these applications, they need to be sterilized. For this, gamma irradiation is the most common method. Thus it is important to evaluate the effects of gamma irradiation on the properties of PCL and PCL/ZnO that have been exposed to gamma irradiation. PCL/Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 30 publications
(52 reference statements)
2
11
0
Order By: Relevance
“…At the add ZnO (1%wt and 5%wt) to PCL the last temperature (Tf) became 493.6°C and 379.3°C for respectively. The Melting temperature decreased of the PCL/ZnO composite due to the decreased crystallization of composites that agree with Paula et al [14].…”
Section: Wettability and Contact Anglesupporting
confidence: 90%
“…At the add ZnO (1%wt and 5%wt) to PCL the last temperature (Tf) became 493.6°C and 379.3°C for respectively. The Melting temperature decreased of the PCL/ZnO composite due to the decreased crystallization of composites that agree with Paula et al [14].…”
Section: Wettability and Contact Anglesupporting
confidence: 90%
“…This finding is important from an industrial point of view, considering that PCL/JWF and PCL/JWF/PCL-g-MA biocomposites begin to solidify at higher temperatures. Literature [48][49][50] reported an increase in T C of PCL upon addition of carbon nanotubes, clay and zinc oxide. However, in the present work, an increase of approximately 7°C in T C of PCL/JWF and PCL/JWF/PCL-g-MA was achieved, adding an abundant residue without surface treatment.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
“…Siqueira et al [26] showed that the montmorillonite clay accelerated the crystallization process of PCL, suggesting a nucleating effect. Paula et al [27] developed PCL nanocomposites with zinc oxide (ZnO). The PCL crystalline melting temperature increased with the addition of up to 1 % ZnO, while a higher content began to decrease the melting temperature.…”
Section: Introductionmentioning
confidence: 99%